The Rate of Seller Correctness in Naming Batik Solo Pattern: Studied in Indonesia Online Marketplace - Berlian Rahmy Lidiawaty; Mohammad Isa Irawan; Raden Venantius Hari Ginardi (Institut Teknologi Sepuluh Nopember, 2020)
Every pattern in batik Solo has different meaning that affects its use. There are patterns for cultural ceremony, including funerals. Therefore, the seller of batik Solo’s product have to be able to give the right title as the name of its product in online marketplace, so the customer will not missw ear the batik in the wrong ceremony. According to the importance of naming batik Solo’s product, this study aims to assess the accuracy of batik Solo pattern naming by sellers in Indonesian online marketplace. Thus the result of it can be used by the buyer as a recommendation where is the best marketplace to purchase the batik Solo product. First, the study collect the images sample from four biggest marketplace in Indonesia; Tokopedia, Bukalapak, Shopee and Lazada. The sample was collected by inputing the name of batik Solo pattern in the marketplace’s search bar. The keywords that have been used to collect the sample are batik parang, batik truntum, batik sawat, batik kawung and batik slobog. Those are the kinds of batik Solo pattern that has different expedience from each other. After 834 samples have been collected, the study assigns whether the seller give the correct name to the batik Solo product or not. The result of this study are the correctness percentage (CP) of the seller in naming their batik Solo product. In general the CP is 82,13%, Marketplace with the highest CP is Lazada (95,42%) and the highest CP of pattern is parang (91%). Beside that, the study also rates marketplace with the parameter of Best Marketplace by Pattern (BMP) and Best Marketplace of Category (BMC). The study divided the parameters to rate marketplace, because the best marketplace that has the highest correctness percentage in one category of a pattern is not always be a marketplace that has the highest correctness percentage in that pattern.